La sensibilité au contraste: une réalité clinique. II. Implications cliniques - Bolduc, M.; Gresset, J. (Canadian Journal of Optometry, 2026)
This article presents clinical applications of contrast sensitivity measurement. The effect of different ocular conditions on contrast sensitivity measurements are reported. 7be study of contrast sensitivity is valuable in many fields of Optometry. Even if this measurement is not necessary in all cases, it may bring useful information and lead to a better description and understanding of visual deficits